Analisis Motivasi Kerja, Disiplin Kerja, dan Kompensasi terhadap Kinerja Karyawan - Surya Ardyansyah; Slamet Widodo (Commodities, Journal of Economic and Business, 2024)
The success of a company is highly influenced by the competence of its human resources. Optimal employee performance is a crucial factor in achieving the company's targets and vision. However, factors such as work motivation, work discipline, and compensation often play a key role in determining performance. This study aims to analyze the influence of work motivation, work discipline, and compensation on employee performance. This research employs a quantitative method with a descriptive approach. The sample consists of 50 employees selected using a total sampling technique. Data were analyzed using multiple linear regression with the help of SPSS software. The results of the study indicate that work motivation, work discipline, and compensation significantly affect employee performance both partially and simultaneously. These findings suggest that improvements in motivation, discipline, and compensation can enhance overall employee performance.